Πάτερ, ημων ο εν τοῖς οὐρανοῖς (Mt 6:9a): Reading the Lord’s Prayer with insight from Ewe cosmology - Sakitey, Daniel; Van Eck, Ernest (Hervormde teologiese studies, 2022)
This article seeks to interpret the phrase Πάτερ, ημων ο εν τοῖς οὐρανοῖς in the invocation of the Lord’s Prayer in the light of Ewe-Ghanaian cosmology. The article employs a combination of the historical-critical and indigenous mother tongue biblical hermeneutical approaches to explore the implication of the invocation for Ewe-Ghanaian Christian spirituality today. The article firstly discusses the various theological and hermeneutical positions of the invocation in dialogue with Ewe-Ghanaian concept of God and the plurality of his dwelling place. The article argues that Matthew’s use of οὐρανοῖς to suggest a plurality in God’s dwelling place resonates with Ewe cosmology, where it is believed that there are seven states of existence and that Mawugã, the Supreme Being, dwells in the first – the absolute state. Thus God exists in ‘seven heavens’ in Ewe cosmology, with the highest heaven being the eternal state of abode. On the other hand, the inclusive interpretation of the fatherhood of God in Ewe cosmology is discontinuous with the exclusive interpretation in the works of the church fathers such as Cyprian, Origen, Gregory of Nissa, Augustine and Clement of Alexandria. This hermeneutical position, the article observes, was responsible for the theological tensions that characterised the encounter between missionary Christianity and Ewe indigenous religion in the middle of the 19th century. However, the introduction of social services as evangelisation strategy, the legacy of the Ewe Bible and liturgy and the handing over of the Ewe church to the indigenous coworkers may have contributed to a large extent in ensuring religious tolerance among followers of the two religions. Today, Ewe-Ghanaian popular Christianity has shifted from its apologetic stance to a more liberal stance and employs indigenous religious and cultural categories in theologising.Contribution: Matthew’s rendition of the invocation of the Lord’s Prayer in the context of Ewe-Ghanaian cosmology is the focus of this article. The article forms part of the researcher’s contribution to the academic knowledge on the Lord’s Prayer and inspires the use of mother tongue biblical hermeneutics in the development of theological materials for the Ewe-Ghanaian Christian communities in Ghana and Togo.